Factors influencing willingness to adopt renewable energy technologies among micro and small enterprises in Lagos State Nigeria - Adepoju, Adeyemi Oluwaseun; Akinwale, Yusuf Opeyemi (International Journal of Sustainable Energy Planning and Management, 2019)
Micro and small enterprises (MSEs) are the engine of economic growth in Nigeria. But they also contribute heavily to the climate change through their choice of energy. Mostly prefer source is the fossil fuel for electricity generation despite the growing awareness of the need to reduce greenhouse gas emissions by embracing renewable energy technologies across the globe. Meanwhile, MSEs accounts for a large proportion of businesses in Lagos State, Nigeria and the situation is not different. Hence, this study investigated the factors influencing willingness to adopt renewable energy technologies among the MSEs. The study surveyed 300 MSEs between January and March, 2017 in Lagos State, Nigeria. Using logit regression, the results showed that creating awareness and knowledge about renewable energy, adequate government policies, trust, peer-effect, development of renewable energy markets and technology acceptance factors (if it makes life easier, simple to use and improve the quality of work) are all positive and statistically significant in influencing the willingness to adopt renewable energy technologies among the MSEs. Cooperation between private enterprises and relevant government agencies supported by ‘political will’ is required to promote the aforementioned factors influencing the willingness to adopt RETs in Nigeria.